Remove Chemical Contaminants from Potable Water by Household Water Treatment System - Teba S. Hussain; Alaa H. Al-Fatlawi (Civil Engineering Journal, 2020)
The Main aim of the present study is to manufacture "Low- Cost Water Filter" for purification water and are designed for small water capacity, using readily available material and environmentally friendly such as kaolin clay, and jute fibers. A number of household treatment systems are readily available in the market. They are differing mainly in make and water purification mechanisms utilized. Most of the available household treatment devices are costly and hence there is a need to come up with cheap or affordable treatment technologies. This research was carried out to determine the efficiency of Kaolin-jute fibers filters in improving water impurities. Types of filters that were used during this study are: Filter 1, build with mixing ratio 85% kaolin clay, and 15% jute fibers, Filter 2: 80% kaolin clay, and 20% jute fibers, Filter 3, 75% kaolin clay, and 25% jute fibers. Effectiveness of these filters in decreasing chemical parameters like Hydrogen Ion Concentration (pH), Chloride (Cl), Calcium (Ca), Total Hardness (T.H), Magnesium (Mg), Alkalinity (ALK), Sulfates (SO4), Sodium (Na), and Potassium (K), were 8.7%, 71.54%, 70.5%, 70.5%, 80.7%, 77.9%, 85.5%, 71.64%, and 69.6% respectively. Kaolin-jute fibers filters can produce enough drinking and cooking water for a family of small members due to their flow rates. These filters may be considered for treating contaminated water at household scale in rural areas and places where water is taken directly from the source without treatment.